Environmental Efficiency, Innovation and Economic Performances. - Montini, Anna (Routledge Explorations in Environmental Economics, v. 25, 2010)
Brings together microeconomics studies on firms' eco and economic performance both in the industrial and service sector; by considering a sector based perspective rooted mainly in the exploitation of NAMEA data; at regional level, and a macroeconomic analysis of the environment, income and welfare.